Optimalisasi Media Sosial Instagram UMKM Mahasiswa Prodi S1 Ilmu Komunikasi UNJ - Safitri, Dini; Romli, Nada Arina (Unri Conference Series: Community Engagement, 2024)
Student MSMEs are generally not managed well. The awareness of students in urban areas like Jakarta is that they do not fully want to develop student-managed entrepreneurship. However, due to several demands from the campus to become entrepreneurs, UNJ communication science undergraduate study program students created student entrepreneurs by optimizing the social media Instagram. There are 10 student MSMEs managed by students from the Bachelor of Communication Science study program. As a marketing tool, they use Instagram social media to market their business products. The aim of this service activity is to help MSME students be able to optimize Instagram social media so that their MSME products can be competitive. The activity method used is project-based learning in copywriting courses. The results of this activity are that students are able to manage Instagram social media and optimize social media by improving the performance of the content produced, getting likes from users and increasing sales of their products.